Empirical analysis on the impacts of carbon sink afforestation project on county industrial structural upgrading - Yishuai Shi; Yuhang Guan; Li Li; Mingrong Huang (Alexandria Engineering Journal, 2022)
The academia has paid much attention to the ecological protection and poverty alleviation functions of carbon sink afforestation project (CSAP), an important means to realize forestry carbon sink. However, whether CSAP can promote county industrial structural upgrading (ISU) and propel high-quality economic development remains unanswered. Based on the panel data of counties in Sichuan Province, China in 2000–2016, this paper estimates the impacts of CSAP on ISU through difference-in-differences with variation in treatment timing (VTT-DID) and synthetic control method. The results show that: CSAP can improve the advanced level of county industrial structure. This finding remains valid after a series of robustness tests. Government guidance dominates the impacts of CSAP on ISU, while market regulation plays a limited role in the impact mechanism due to the presence of elite capture. Government guidance and market regulation have a positive synergistic effect. The ISU impacts of CSAP are affected by resource endowment, level of economic development, and culture difference of ethnic monitories at the county level. Mechanism analysis shows that CSAP mainly acts on county ISU by increasing capital accumulation. The research results provide a reference path for China to transform its concept of economic development, and the key evidence for the fact that CSAP is an important way to realize high-quality economic development and environment protection at the county level.